Surgical Treatment of Another Sequalae of COVID-19: Post-COVID CTEPH - Ermerak, Nezih Onur; Yildizeli, Sehnaz Olgun; Kocakaya, Derya; Mutlu, Bulent; Ak, Koray; Tas, Serpil; Yildizeli, Bedrettin (The Thoracic and Cardiovascular Surgeon, 2023)
Background Coronavirus disease 2019 (COVID-19) is still an ongoing entity and every day we face new sequalae of the disease. We hereby present surgical results of patients who are treated for post-COVID chronic thromboembolic pulmonary hypertension.Methods Data were collected among patients who underwent pulmonary endarterectomy and had a diagnosis of post-COVID chronic thromboembolic pulmonary hypertension. All data were retrospectively reviewed from a prospectively conducted database. Operative mortality was described as death in hospital or within 30 days of surgery.Results Eleven patients (seven males, four females; median age, 52 [22–63] years) were identified. Pulmonary vascular resistance improved significantly from 572 dyn/s/cm−5 (240–1,192) to 240 (195–377) dyn/s/cm−5 (p < 0.005). Significant difference was also detected in median mPAP, as it decreased from 40 mm Hg (24–54) to 24 mm Hg (15–36) following surgery (p < 0.005). Mortality was observed in one patient due to sepsis on the fifth postoperative day. Median time from COVID-19 disease to surgery was 12 months (6–24). Median length of hospital stay of the survivors was 10 days (8–14).Conclusion In the new era of chronic thromboembolic pulmonary hypertension, hybrid approach including surgery, balloon pulmonary angioplasty, and medical treatment has been recommended. pulmonary endarterectomy is still the only curative treatment when the disease is surgically accessible. We hereby report the first publication of post-COVID chronic thromboembolic pulmonary hypertension patients who were surgically treated. As we see a lot of long-term symptoms and clinical manifestations in patients who had COVID-19, we should always remember chronic thromboembolic pulmonary hypertension in the differential diagnosis.
Keywords: COVID-19; chronic thromboembolic pulmonary hypertension; post-COVID; long COVID; pulmonary endarterectomy